The academic's and policy-maker's guides to the teaching research nexus : a suite of resources for enhancing reflective practice : final project report. - Krause, Kerri-Lee; Arkoudis, Sophie; James, Richard; McCulloch, Ros; Jennings, Claire; Green, Alison (Australian Learning and Teaching Council, 2008)
This report outlines the findings from the two year national project on the teaching-research nexus (TRN). The team comprised Professor Kerri-Lee Krause (project leader), Dr Sophie Arkoudis, Professor Richard James, Ms Ros McCulloch, Ms Claire Jennings and Dr Alison Green. Project outcomes are based on interviews with academics, policy-makers and students across eight Australian universities. In addition, the team reviewed existing literature and consulted with national and international experts to develop a Guide on best practice in relation to teaching-research connections for academics and policy-makers.